Children’s food habits, consumption, and food safety of popular snacks in school environment in Indonesia - Khomsan, Ali; Anwar, Faisal; Riyadi, Hadi; Navratilova, Hana F. (International Journal Of Community Medicine And Public Health, 2022)
Background: School age is a period of children's growth and development into adolescence. Therefore, an adequate intake of nutrients and food that is safe to consume is essential. The food safety level of school snacks is still poor. Good snacking habits can contribute enough energy and protein to children. Conversely, improper and unhealthy snacking habits can have negative impacts on children. Methods: This cross-sectional study was conducted in six selected public elementary schools from January 2018 until April 2019. The study involved selecting a sample using the purposive sampling method. The total samples from six schools were 214 students. Results: The study found a significant difference between eating frequency of school children in urban and rural areas (p<0.05). Regarding snacking habits, most students in urban (61.0%) and rural (76.2%) had snacks 4-6 times per week. Snack’s contribution to daily energy and protein intake in rural was 21.7% for energy and 18.1% for protein, while in rural, 31.6% for energy and 24.1% for protein. The results of the microbiological contamination analysis of popular snacks from all of the schools came out negative. Conclusions: Based on those findings, the schools should continuously supervise the practice of selling snacks around the school. The department of education and culture and the health office need to conduct training for food vendors and teachers about healthy snacks in schools. Parents need to pay more attention to children's food consumption.